Inverse relationship between percentage body weight change and finishing time in 643 forty-two-kilometre marathon runners. Issue 14 (15th December 2010) - Zouhal, Hassane; Groussard, Carole; Minter, Guenolé; Vincent, Sophie; Cretual, Armel; Gratas-Delamarche, Arlette; Delamarche, Paul; Noakes, Timothy David
Abstract : Objective: The purpose of this study was to determine the relationship between athletic performance and the change in body weight (BW) during a 42 km marathon in a large cohort of runners. Methods: The study took place during the 2009 Mont Saint-Michel Marathon (France). 643 marathon finishers (560 males and 83 females) were studied. The change in BW during the race was calculated from measurements of each runner's BW immediately before and after the race. Results: BW loss was 2.3±2.2% (mean±SEM) (p<0.01). BW loss was −3.1±1.9% for runners finishing the marathon in less than 3 h; −2.5±2.1% for runners finishing between 3 and 4 h; and −1.8±2.4% for runners who required more than 4 h to complete the marathon. The degree of BW loss was linearly related to 42 km race finishing time (p<0.0000001). Neither age nor gender influenced BW loss during the race. Conclusions: BW loss during the marathon was inversely related to race finishing time in 643 marathon runners and was >3% in runners completing the race in less than 3 h. These data are not compatible with laboratory-derived data suggesting that BW loss greater than 2% during exercise impairs athletic performance. They match an extensive body of evidence showing that the most successful athletes in marathon and ultra-marathon running and triathlon events are frequently those who lose substantially more than 3–4% BW during competition.